2011
DOI: 10.4049/jimmunol.1004175
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Induced by Apoptotic Antigen-Coupled Leukocytes Is Induced by PD-L1+ and IL-10–Producing Splenic Macrophages and Maintained by T Regulatory Cells

Abstract: Antigen-specific tolerance is a highly desired therapy for immune-mediated diseases. Intravenous infusion of protein/peptide antigens linked to syngeneic splenic leukocytes with ethylene carbodiimide (Ag-SP) has been demonstrated to be a highly efficient method for inducing peripheral, antigen-specific T cell tolerance for treatment of autoimmune disease. However, little is understood about the mechanisms underlying this therapy. Here, we show that apoptotic Ag-SP accumulate in the splenic marginal zone where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
260
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(279 citation statements)
references
References 56 publications
15
260
0
Order By: Relevance
“…The use of apoptotic cells to induce tolerance was uncovered originally in 1979 [79] and has shown promise in an early clinical study [80], However, the use of cells has numerous manufacturing, cost, and patient accessibility issues. The serendipitous discovery that negatively charged NPs target specific scavenger receptors and localize to the same regions of the spleen, similar to apoptotic cells, catalyzed the development of a synthetic cell replacement that could carry antigen for immune tolerance induction [6,8,81]. Subsequently, several NP-based approaches for the induction of immune tolerance that function via alternative mechanisms have emerged.…”
Section: Nps For Immune Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…The use of apoptotic cells to induce tolerance was uncovered originally in 1979 [79] and has shown promise in an early clinical study [80], However, the use of cells has numerous manufacturing, cost, and patient accessibility issues. The serendipitous discovery that negatively charged NPs target specific scavenger receptors and localize to the same regions of the spleen, similar to apoptotic cells, catalyzed the development of a synthetic cell replacement that could carry antigen for immune tolerance induction [6,8,81]. Subsequently, several NP-based approaches for the induction of immune tolerance that function via alternative mechanisms have emerged.…”
Section: Nps For Immune Tolerancementioning
confidence: 99%
“…Tolerogenic IMPs (TIMPs) were designed to take advantage of the MARCO-targeting ability of highly negatively charged NPs [8,89]. The intravenous administration of antigen-encapsulated IMPs results in biodistribution similar to that of apoptotic debris [6,81], with particles homing to MARCO+ macrophages in the liver and spleen (Figure 2) [6,8,9,81]. More importantly, one course of TIMPs results in tolerance induction through T cell anergy and the parallel induction of Tregs [90].…”
Section: Np Development For Tolerancementioning
confidence: 99%
“…Strategies to induce tolerance include conjugating antigen to splenocytes [8], immature dendritic cells (DC) [9,10], or synthetic microparticles [11,12], oral tolerance [13], gene therapy [14] or co-treatment with immunosuppressive drugs, such as methotrexate [15]. Recently, it has been reported that systemic co-administration of rapamycin, a immunosuppressant drug commonly used to prevent transplant rejection, prevented immune response and induced tolerance to FIX and FVIII in mouse models of hemophilia A and B, respectively [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the scavenger role of splenic macrophages for aged red cells is known to every medical student, while the recent tolerising role of macrophages such as the F4/80 þ macrophages in the mouse has been revealed. 73 The new and interesting information on heterogeneity in macrophages, some with inflammatory functions, others with anti-inflammatory roles, is highly relevant to disease in the eye, such as AMD, diabetes, and uveitis and probably many other conditions associated with the degenerative diseases of ageing. The balance of outcome seems to depend on whether the effects of low level chronic inflammation are more or less deleterious to the host compared with the potentially destructive effects of the healing response, which are more than amply played out in the retina.…”
Section: Innate Immunity and The Danger Hypothesismentioning
confidence: 99%